Factors Affecting Housing Affordability among the Middle-Income Group in Selangor - Wilson Rangga, Anthony Jiram; Azizah, Ismail; Vuan Teng, Soh (2022)
This study aims to determine the factors affecting housing affordability among the middle-income group in Selangor and rank the factors affecting the housing affordability for this group. Malaysia has experienced rapid urban growth with the increase of urban population due to urbanisation and rapid economic activities since the 1950s. The rapid urban growth increases the population in the urban area, leading to increased income levels and migration. This phenomenon has undoubtedly affected the housing sector in the country. The housing sector in Malaysia has experienced fluctuating prices as the demand for housing in the market increase. As house purchase is influenced by affordability, it is important to understand and determine factors influencing the perception of affordability among middle-income households to provide affordable housing for this group. The scope of this research concentrates on the middle-income group in Selangor. The questionnaire was distributed to 100 respondents from the middle-income group in Selangor. The data from the questionnaire were analysed using descriptive analysis and Relative Importance Index (RII) analysis. The study found six factors affecting housing affordability among the middle-income group in Selangor: house price, monthly income, housing loan, location, number of working adults in a household, and health status.